GOLD-PALLADIUM MINERALIZATION AT BLEïDA FAR WEST, BOU AZZER-EL GRAARA INLIER, ANTI-ATLAS, MOROCCO - Ghorfi M.; Oberthür T.; Melcher F.; El Boukhari A.; Lüders V.; Maacha L.; Ziadi R.; Baoutoul H. (My University, 2006)
The structurally controlled Au-Pd mineralization at Bleïda Far West occurs in a volcano-sedimentary rock sequence in altered amphibolites and chlorite schists of the Neoproterozoic Bou Azzer-El Graara inlier. The Au-Pd mineralization is virtually sulfide-free; instead, gold is associated with hematite, barite, quartz, and calcite. The gold grains are silver- and palladium-bearing (up to 19 wt% Ag and 6.3 wt% Pd) and are intergrown with a distinct suite of mainly Pd-dominated platinum group minerals, namely mertieite-I/isomertieite, merenskyite, keithconnite, kotulskite, palladseite, and sperrylite, defining a Au-Pd-As-Sb-Se-Te chemical signature. Stable isotope and fluid inclusion studies indicate a wide range of fluid compositions with a prominent saline component. In conjunction with the mineral association, oxidizing fluids are indicated, and Au and PGE transport and deposition likely took place by chloride complexes in the epithermal range, at elevated fO2 and/or low pH. It is still speculative whether the mineralization is late Pan-African (~600-550 Ma) in age, or connected with the Variscan orogeny (~330-300 Ma), or related to some other hydrothermal event. Common to all Au-Pd mineralizations worldwide (Brazil, Australia, UK), including Bleïda Far West, is their formation in the epithermal (<300°C) range; deposition mainly in brittle structures; sulfide-poor mineral assemblages comprising hematite, sulfate minerals, and selenides; and metal transport by, and deposition from, oxidized, chloride-rich fluids. These deposits are further characterized by noble metal abundances in the order Au>Pd>Pt and the chemical signature Au-Pd-Se-Te (±As, Sb, Bi). As such, the Au-Pd association represents a discrete style of gold mineralization distinct from other classes of gold deposits. © Springer-Verlag 2006.
Keywords: ANTI-ATLAS; BLEïDAFAR WEST; GOLD-PALLADIUM MINERALIZATION; MOROCCO; PALLADIANGOLD; PLATINUM-GROUP MINERALS; Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская